ESG Performance Ranking With A New Hybrid Decision Making Model: Application Of The CRISUS-PIV Hybrid Model For The Banking Sector (Third Sector Social Economic Review, 2025)
In recent years, with the rise of the sustainable finance approach, environmental, social and governance (ESG) criteria have increasingly found a place in the corporate strategies of financial institutions. In particular, the banking sector plays an important role in economic, environmental and social sustainability through its direct and indirect impacts. In this context, measuring and evaluating the ESG performance of banks is of great importance both in terms of monitoring their corporate responsibilities and analyzing their long-term value creation capacity. This study aims to analyze the environmental, social and governance (ESG) performance of Yapı ve Kredi Bank A.Ş., which operates in the banking sector in Turkey, for the period between 2011 and 2022 with a comprehensive approach. The weights of the 10 ESG performance criteria identified in the analysis were calculated objectively using the Criterion Importance Based on Sum of Squares (CRISUS) method, and then an ESG performance ranking was created using the Proximity Index Value (PIV) procedure. According to the results of the CRISUS method, the three most important criteria are D8à(Governance), D2à(Emissions), D9à(Shareholders). According to the results of the PIV method, the most successful periods in the ESG performance of Yapı ve Kredi Bank A.Ş. were determined as 2022, 2021 and 2020, respectively. Additionally, sensitivity analyses were conducted to test the reliability of the proposed hybrid decision-support model, confirming its effectiveness in financial performance evaluation.
Keywords: CRISUS; PIV; MCDM; ESG; Performance